PERAN GURU BK DALAM MEMBERIKAN LAYANAN INFORMASI TENTANG PERENCANAAN MASA DEPAN UNTUK MENCEGAH TERJADINYA ANTISIPATORI PADA SISWA KELAS X-E12 MAN 1 SURAKARTA TAHUN PELAJARAN 2024/2025 - Hera Heru Sri Suryani; Aditya Wahyu Eka Prasetya; Ahmad Jawandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Future planning information services are provided to students to prevent anticipatory. Through motivation and guidance, students are expected to understand the conditions they face so that it is easier to determine their future. The purpose of this study is to determine the role of the Guidance and Counseling Teacher at MAN 1 Surakarta in the Process of Preventing Anticipatory in MAN 1 Surakarta, especially for class X-E12 students in the 2024/2025 Academic Year. This descriptive qualitative study uses interviews, observations, and documentation, with validity tests through source and time triangulation. Data analysis is carried out through reduction, presentation, and drawing conclusions. The results of the study indicate that information services for class X-E12 students at MAN 1 Surakarta increase understanding of the meaning, characteristics, causes, and ways to overcome anticipatory. Guidance and Counseling teachers play an active role in creating a motivating atmosphere so that students are enthusiastic, understand the material, and are involved in the service process.